Rapid fluoroquinolone resistance detection in Pseudomonas aeruginosa using mismatch amplification mutation assay-based real-time PCR. Issue 10 (27th October 2022) - Madden, Danielle E.; McCarthy, Kate L.; Bell, Scott C.; Olagoke, Olusola; Baird, Timothy; Neill, Jane; Ramsay, Kay A.; Kidd, Timothy J.; Stewart, Adam G.; Subedi, Shradha; Choong, Keat; Fraser, Tamieka A.; et al.
Abstract : Background. Antimicrobial resistance (AMR) is an ever-increasing global health concern. One crucial facet in tackling the AMR epidemic is earlier and more accurate AMR diagnosis, particularly in the dangerous and highly multi-drug-resistant ESKAPE pathogen, Pseudomonas aeruginosa . Objectives. We aimed to develop two SYBR Green-based mismatch amplification mutation assays (SYBR-MAMAs) targeting GyrA T83I ( gyrA 248) and GyrA D87N, D87Y and D87H ( gyrA 259). Together, these variants cause the majority of fluoroquinolone (FQ) AMR in P. aeruginosa . Methods. Following assay validation, the gyrA 248 and gyrA 259 SYBR-MAMAs were tested on 84 Australian clinical P. aeruginosa isolates, 46 of which demonstrated intermediate/full ciprofloxacin resistance according to antimicrobial susceptibility testing. Results. Our two SYBR-MAMAs correctly predicted an AMR phenotype in the majority (83%) of isolates with intermediate/full FQ resistance. All FQ-sensitive strains were predicted to have a sensitive phenotype. Whole-genome sequencing confirmed 100 % concordance with SYBR-MAMA genotypes. Conclusions. Our GyrA SYBR-MAMAs provide a rapid and cost-effective method for same-day identification of FQ AMR in P. aeruginosa . An additional SYBR-MAMA targeting the GyrB S466Y/S466F variants would increase FQ AMR prediction to 91 %. Clinical implementation of our assays will permit more timely treatment alterations in cases where decreased FQ susceptibility is identified, leading to improved patient outcomes and antimicrobial stewardship.